A novel process for axial closed extrusion of ring part with mesh-like ribs. (1st January 2020) - Tian, Duanyang; Han, Xinghui; Hua, Lin; Huang, Bo; Yang, Siwei
Highlights: The axial closed extrusion (AC E) process is proposed and designed to form high-performance ring part with mesh-like ribs. Through establishing the mechanical models of punch instability and sleeve fracture, the stable work conditions of ACE are obtained, and the required forming force is theoretically estimated. Both ring part with mesh-like ribs and forming dies are properly designed as well as ring billet. The narrowed experimental setup of ACE with a ratio of 4 is designed and carried out to verify the feasibility of ACE and the validation of the established FE model. On the basis of the reliable FE model, the forming mechanisms of ACE of ring part with mesh-like ribs under the SPM and DPM modes are revealed by investigating the metal flow behaviors, the effective stress/strain distribution, the temperature distribution and the forming force variation. Abstract: Fabrication of high-performance ring parts with mesh-like ribs becomes the focus of concern in aerospace industry. The axial closed extrusion (ACE) process is proposed in this work to manufacture this kind of parts. The processes for ACE of ring part with mesh-like ribs under the single punch motion (SPM) and double punches motion (DPM) modes are designed, which innovatively adopts the integrated mold consisting of several equal circular-arc-shaped dies to smoothly extract the extruded ring part with mesh-like ribs from moulds. The stress state in the deformed workpiece in the process of ACE is analyzed, and the critical conditions of both punch instability and sleeve fracture are obtained. In accordance with the stable conditions of ACE, ring part with mesh-like ribs, billet and moulds are precisely designed as well as the stroke of punch. The FE model for ACE of ring part with mesh-like ribs is established by using dynamic explicit DEFORM-3D software, the accuracy of which is validated by the narrowed experiments with a ratio of 4. By means of the reliable FE model, the metal deformation behaviors in the process of ACE under the SPM and DPM modes are comparatively analyzed. Results show that in ACE of ring part with mesh-like ribs the deformation at longitudinal rib is more inhomogeneous than that at transverse rib, and the growth speed of transverse rib is larger than that of longitudinal rib. Compared to the SPM mode, the effective strain under the DPM mode is smaller and distributed more homogeneously, and the temperature in the final extruded part under the DPM mode is lower and distributed more regularly. The forming force under the SPM mode is larger than that under the DPM mode, and the forming force markedly ascends with the increase of the extrusion speed. The results of numerical analysis and experiments demonstrate that the ACE process proposed in this paper is feasible and it has great potential to form ring part with mesh-like ribs.